Study of adaptation of displaced people to the new Conditions of life activity - Sargsyan, Levon (Զանգակ հրատ.)
In the modern world, despite the trends of civilization, humanity experiences many socio-psychological crises, wars, displacements, etc. From a socio-psychological point of view, the war and, consequently, the displacement have become severe traumatic realities for the Armenian society, particularly the Artsakh Armenians. Because of the Artsakh issue, for 30 years, the Armenians have been the bearer of wars, losses, and displacements. In the fall of 2020, the new Artsakh-Azerbaijani war left severe consequences on the life of society: human and territorial losses, displacement, etc. So taking into consideration the created situation, from the socio-psychological point of view, we prioritise the study of the problems of adapting the displaced people to the new environment. From this point of view, we consider the problem we are studying to be topical. The research results show that in the new conditions of life, self-acceptance is of decisive importance for the displaced people to achieve a certain result in life, self- realization correspondingly self-satisfaction.
Keywords: Psychology